Recent applications of linear analysis techniques. - Gibbard, M.J (IEEE Transactions on power systems)
This paper is based on material presented at the Panel Session: Recent Applications of Linear Analysis Techniques conducted during the 1998 IEEE PES Summer Meeting. The topics discussed include: control system design; system identification; large scale system applications; simultaneous coordination of power system stabilisers and FACTS controllers; robust power system stabilisation; small signal stability analysis based on time-domain identified models; EM transient studies modal analysis; and power system dynamics nonlinearities, normal forms method